The role of good faith in contract law good faith and unfair contracts in South Africa and Germany-a comparative approach - Ringleben, Claas (Department of Private Law, 2026)
Good faith is irritating legal systems all over the world, the more so since the principle continuously finds way into various agreements applicable to both national and international transactions. The logical consequence thereof is - or will be - that legal systems that are so far unfamiliar with the principle are forced to employ it to the dispute in question. This fact applies irrespective of its open recognition or its vehement or modest rejection. Whereas Germany openly recognises good faith as one of the most important aspects of its contract law in various modi operandi, South African law, in contrast, contains no such general principle of good faith, although it does have an implicit or undisclosed principle of that sort.